Person Deixis Used By James Corden in The Late Late Show - I Dewa Ayu Gita Wardaning Putri; Ayomi, Putu Nur; Maharani, Putu Devi (Prodi Sastra Inggris Fakultas Bahasa Asing Universitas Mahasaraswati Denpasar, 2022)
This study focuses on the person deixis used by James Corden in his utterances on the talk show The Late Late Show. The theory used in classifying the types of deixis and the category of person deixis found in this study is based on Levinson's (1983) deixis theory. Based on observations, person deixis is the most dominant type of deixis found in James Corden's speech on this talk show. The use of the type of person deixis used by James Corden is absolutely influenced by certain factors. Therefore, this study aims to describe how James Corden uses each category of person deixis and the factors that influence its use in talk shows. This research is limited to using only one episode of The Late Late Show and only examines the person deixis used by James Cordon. This qualitative study used observation methods for data analysis. There are 152 person deixis data used by James Corden in this talk show, which belong to the following categories of person deixis: singular first person deixis, plural first person deixis, singular second person deixis, plural second person deixis, singular third person deixis, and plural third person deixis. In addition, there are factors that influence the use of person deixis expressions, namely topics, situations, power, closeness and formality, and the speaker's goals.